Hospitalization and survival of solid organ transplant recipients with coronavirus disease 2019: A propensity matched cohort study. - Joshua T Swan; Elsie Rizk; Stephen L Jones; Nwabunie Nwana; Juan C Nicolas; Anh Thu Tran; Jiaqiong Xu; Tariq Nisar; Terri Menser; Stephanie G Yi; Linda W Moore; Howard J Huang; et al. (PLoS ONE, 2022)
Background Solid organ transplant (SOT) recipients are predicted to have worse COVID-19 outcomes due to their compromised immunity. However, this association remains uncertain because published studies have had small sample sizes and variability in chronic comorbidity adjustment. Methods In this retrospective cohort study conducted at a multihospital health system, we compared COVID-19 outcomes and survival up to 60 days following hospital admission in SOT recipients taking baseline immunosuppressants versus hospitalized control patients. Results The study included 4,562 patients who were hospitalized with COVID-19 (108 SOT recipients and 4,454 controls) from 03/2020 to 08/2020. Mortality at 60 days was higher for SOT recipients (17% SOT vs 10% control; unadjusted odds ratio (OR) = 1.74, 95% confidence interval (CI) 1.04-2.91, P = 0.04). We then conducted a 1:5 propensity matched cohort analysis (100 SOT recipients; 500 controls) using age, sex, race, body mass index, hypertension, diabetes, chronic kidney disease, liver disease, admission month, and area deprivation index. Within 28 days of admission, SOT recipients had fewer hospital-free days (median; 17 SOT vs 21 control; OR = 0.64, 95%CI 0.46-0.90, P = 0.01) but had similar ICU-free days (OR = 1.20, 95%CI 0.72-2.00, P = 0.49) and ventilator-free days (OR = 0.91, 95%CI 0.53-1.57, P = 0.75). There was no statistically significant difference in 28-day mortality (9% SOT vs 12% control; OR = 0.76, 95%CI 0.36-1.57, P = 0.46) or 60-day mortality (16% SOT vs 14% control; OR = 1.15, 95%CI 0.64-2.08, P = 0.64). Conclusions Hospitalized SOT recipients appear to need additional days of hospital care but can achieve short-term mortality outcomes from COVID-19 that are similar to non-SOT recipients in a propensity matched cohort study.